Telecommunications and WTO discipline : an assessment of the WTO agreement on telecommunication services. - FREDEBEUL-KREIN (1997)
Analyses the results of the WTO agreement on basic telecommunication services. Argues that the major shortcoming of the WTO accord is that member countries are not obliged to apply most-favoured-nation treatment to all other members, and that commitments on national regulatory policies are not detailed enough to make competitive market access become a reality.